Language and Culture - Stanley, Carole A. (Papers from the Annual Meetings of the Atlantic Provinces Linguistic Association (PAMAPLA) / ACTES DES COLLOQUES ANNUELS DE L’ASSOCIATION DE LINGUISTIQUE DES PROVINCES ATLANTIQUES (ACAALPA)., 1994)
Edward Sapir and his student Benjamin Whorf suggested that “language is a force in its own right—that it affects how individuals in a society perceive and conceive reality” (Ember & Ember 1988:227). While this is an intriguing hypothesis, it fails to account for the fact that certain groups who speak closely-related languages have vastly different cultural beliefs and practices. Plog and Bates (1980:210) cite as examples of this the southwestern Navaho and the Hupa and Apache. The Navaho, a highly ritualized culture, have little in common with the loosely-organized hunting-and-gathering Hupa or the highly competitive Apache. And yet, all three of these groups speak variants of the same language. The position taken in this paper is that language is a reflection of the beliefs and practices of the people who speak it. An attempt will be made to show how the culture of the Tikar people of Cameroon, West Africa, is reflected in their language.1